2016
DOI: 10.1016/j.jpainsymman.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

What Aspects of Quality of Life Are Important From Palliative Care Patients' Perspectives? A Systematic Review of Qualitative Research

Abstract: A broad range of domains are important to the QOL of people with life-limiting illnesses receiving palliation. Refinement of measures is needed to help ensure services address issues valued by patients such as preparation for death and aspects of health care provision, elements which are seldom included in currently available preference-based measures used to inform value for money decisions in palliative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 63 publications
2
89
0
4
Order By: Relevance
“…Because of this limitation, and the plausible notion that chaplaincy consultation is a phenomenon occurring naturally as a psychologic need in the EOL setting, we interpret our finding of an association between chaplaincy consultation and late admission with caution. This is an issue that merits prospective study, especially given that spiritual support is a vital component of EOL care (41), and because our findings are at odds with prior studies as mentioned above. (34) Finally, some patients followed to death at our center were not included by virtue our inclusion criteria.…”
Section: Discussionmentioning
confidence: 57%
“…Because of this limitation, and the plausible notion that chaplaincy consultation is a phenomenon occurring naturally as a psychologic need in the EOL setting, we interpret our finding of an association between chaplaincy consultation and late admission with caution. This is an issue that merits prospective study, especially given that spiritual support is a vital component of EOL care (41), and because our findings are at odds with prior studies as mentioned above. (34) Finally, some patients followed to death at our center were not included by virtue our inclusion criteria.…”
Section: Discussionmentioning
confidence: 57%
“…Studies have demonstrated the importance of dignity in the dying process and its interrelationship with patient autonomy. 24,29 A desire to promote a patient's or surrogate decision-maker's autonomy in such situations may contribute to a physician's consideration of patient wishes, especially with regard to minimally invasive interventions such as antimicrobial therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that measures need to be refined to identify issues the patients value, such as the preparation for death and aspects inherent in health care provision, among others, which the instruments available in the literature often do not address 20 . In addition, it is known that the determining factors of cancer patients’ quality of life often are not well understood 21 .…”
Section: Discussionmentioning
confidence: 99%